EFEKTIVITAS PENGGUNAAN MEDIA POWER POINT DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS III-A SD NEGERI 11 CAKRANEGARA - MURTINI, NI KOMANG (GANEC SWARA, 2019)
This research is a classroom action research consisting of two cycles where each cycle consists of four stages, namely the stages of planning, implementation, observation, and reflection. Each cycle consists of 3 meetings.     This study aims to determine whether using power point media in PBM can improve Mathematics learning achievement in Class III-A Students at SD Negeri 11 Cakranegara Semester I Academic Year 2017/2018. The place of research in SD Negeri 11 Cakranegara, for 6 (six) months from July to December 2017 with research subjects of class III-A students totaling 27 people.     Data collection techniques used by observation, evaluation, and documentation. While the data analysis technique is qualitative descriptive. In the study, the final success indicator for student learning achievement was set at 85% of students reaching 70. The indicator was reached in the second cycle, so the action research was carried out in 2 cycles where each cycle consisted of 3 (three) meetings.     The results of the study showed that after the use of power point media in PBM, the student learning achievement increased by 8.7% with an average value in the first cycle of 68.15 and in the second cycle it increased to 76.85. While for learning completeness there was an increase of 29.63% from the first cycle of 62.96% and in the second cycle it increased to 92.59%. Thus, the use of Power point media in PBM can effectively improve student achievement, especially students of class III-A on Mathematics subjects at SD Negeri 11 Cakranegara.